A narrative review of research on clinical responses to the problem of sexual offenses in the last decade. (6th February 2020) - Ly, Thanh; Fedoroff, J. Paul; Briken, Peer
Abstract: Research on the treatment and programs for people who have committed sexual offenses has greatly increased in the past decade. The aim of this review is to discuss research that has been published over that period (2010–2019) that is relevant for treatment providers. The articles included in this review were found through PsycINFO and PubMed (Medline) using the keywords "treatment or therapy" and "sex offen*". The inclusion criteria were publications that discuss treatment of persons who have committed sexual offenses (written in the English language only). Any articles that examined only special populations were excluded, such as those that examined persons who committed sexual offenses who were female, had intellectual disabilities, deafness, juveniles, etc., because these groups will likely have needs and responsivity factors that differ from the "average" natal‐born male sex offender. Results showed that several meta‐analyses indicate that treatment is effective in reducing sexual recidivism. The most frequently used treatment for sex offenders is cognitive behavioral therapy, which is often provided in conjunction with pharmacological treatment to reduce sexual impulsivity and/or sex drive. This review is limited to the specific key search terms. The findings of this review support the use of treatment and a community reintegration approach when treating persons who have committed sexual crimes to prevent sexual recidivism.